A comprehensive study on the structural, morphological, compositional and optical properties of ZnxCd1−xS thin films. (15th January 2020) - Barman, Biswajit; Bangera, Kasturi V; Shivakumar, G K
Abstract: The absorption loss in cadmium sulfide (CdS) thin films which are widely used as a window layer in a photovoltaic cell limits the efficiency of the device. This issue can be addressed by Znx Cd1−x S thin films due to its tunable band gap nature. Herein, the various composition of Znx Cd1−x S (x=0, 0.15, 0.30, 0.45, 0.70, 0.85, 1) thin films were grown by a vacuum thermal evaporation technique and the characteristics of the films were investigated by varying the composition 'x'. The x-ray diffraction (XRD) studies displayed that the as-deposited films consist of diffraction peaks from both CdS and ZnS lattice. The formation of ternary Znx Cd1−x S films was verified when the deposited films were subjected to an annealing treatment. The morphology of the films was analyzed using a scanning electron microscope (SEM) and it was observed that the films are uniform, homogeneous and free from any pin-holes and cracks. The presence of Zn, Cd and S elements were quantized using an energy dispersive spectroscopy. Optical studies showed a successful non-linear band gap engineering (2.42–3.49 eV) for the deposited Znx Cd1−x S thin films. All films showed a very high optical transmittance of above 70% in the visible wavelength region.